An X-ray Experiment with Two-Stage Korean Sounding Rocket - Uk-Won Nam; Chul-Sung Choi (Journal of Astronomy and Space Sciences, 1998)
The test result of the X-ray observation system is presented which have been developed at Korea Astronomy Observatory for 3 years (1995-1997). The instrument, which is composed of detector and signal processing parts, is designed for the future observations of compact X-ray sources. The performance of the instrument was tested by mounting on the two-stage Korean Sounding Rocket, which was launched from Taean rocket flight center on June 11 at 10:00 KST 1998. Telemetry data were received from individual parts of the instrument for 32 and 55.7 sec, respectively, since the launch of the rocket. In this paper, the result of the data analysis based on the telemetry data and discussion about the performance of the instrument is reported.